Unravelling the synergistic effect of multiscale hierarchical material architecture for enhanced urea adsorption - Yen, Zhihao (2025)
Adsorption of inert small molecules has always been challenging and hence these molecules are generally difficult to remove from solution. In this work, we demonstrated a significant improvement (>25 times) in the adsorption of an inert small molecule, urea, using a hierarchical material design, which remarkably outperformed the simple chemical functionalization of the substrate. To illustrate this point, we employed two-dimensional (2D) materials such as Ti3C2Tx MXene as the adsorbent “substrate” which has a high potential for efficient urea removal. In particular Cu-functionalized MXene, with Cu valency between 0 and +1 exhibited superior urea adsorption performance compared to pristine MXene. However, due to the strong van der Waals forces, MXene has a propensity to aggregate, leading to the loss of active sites for urea adsorption. To address this, cellulose nanocrystals were introduced as it has dual functionalities; namely to prevent aggregation and preserve active sites for adsorption of urea. These nanocrystals are small, rigid, and hydrophilic, facilitating their interaction with hydrophilic groups on the MXene surface. Porous hydrogel macrobeads prepared using alginate crosslinked with calcium ions yielded a hierarchical structure with nanosized MXene-cellulose moieties distributed within the millimetre beads. Besides serving as mechanical support, the cellulose nanocrystals can be further surface-functionalised with enhanced interaction with chemical groups such as polydopamine to boost the adsorption properties. Each component in the hydrogel composite synergistically enhanced the interaction with urea and promoted adsorption. Consequently, the composite hydrogel exhibited a remarkable enhancement in urea adsorption capacity from 6.7 to 354.4 mg/g in aqueous solution, while a Qmax of 115.1 mg/g was observed in simulated dialysate solution due to the increased surface area available for urea adsorption. The development of this hydrogel composite consisting of Cu-functionalized MXene, functionalized cellulose nanocrystals, and alginate crosslinking with calcium, showcased its potential as a highly efficient and versatile material for effective urea adsorption in both aqueous and simulated dialysate solutions.